PENGARUH WEBSITE DESAIN, RELIABILITY DAN PERCEIVED EASE OF USE DALAM MEMBAGUN E-TRUST DAN E-RETENTION - Davinariyan Mohammad Thirafi; Ayu Ekasari (EBID: Ekonomi Bisnis Digital, 2025)
This study aims to analyze the influence of website design, reliability and perceived ease of use on e-trust and e-retention as well as the mediation effect of e-trust. The study was conducted using a quantitative approach and survey method by taking samples of marketplace users. The design in this study was carried out through hypothesis testing. Data collection took place cross-sectionally. The data is primary data and was collected by distributing questionnaires via google form which were filled out by 200 participants studied. Data processing techniques used include instrument testing such as validity and reliability tests, structural equation modeling (SEM), and descriptive statistical tests using SPSS and AMOS software. The results of the study indicate that website design does not affect e-trust in online shopping, website design affects e-retention in online shopping, reliability affects e-trust but does not affect e-retention in online shopping, perceived ease of use affects E-trust in online shopping. Furthermore, E-trust in online shopping mediates the influence of reliability and perceived ease of use.